Citizenship Laws and International Migration in Historical Perspective - Graziella Bertocchi; Chiara Strozzi (Fondazione Eni Enrico Mattei (FEEM), 2005)
We investigate the origin, impact and evolution of citizenship laws. Citizenship laws originate from the common and civil law traditions, which apply jus soli and jus sanguinis, respectively. We compile a data set across countries of the world starting from the 19th century. The impact of the original, exogenously-given laws on international migration proves insignificant for the early, mass migration waves, which confirm to be driven primarily by economic incentives. Postwar convergence of citizenship laws is determined by legal tradition and international migration, but also by border stability, the establishment of democracy, the welfare burden, cultural factors and colonial history.
Keywords: F22; K40; N30; O15; 330; Citizenship laws; International migration; Legal origins; Democracy; Borders